Pengaruh Lingkungan Kerja Fisik dan Budaya Organisasi terhadap Kepuasan Kerja pada Pegawai PT Aneka Tambang Tbk UBPP Logam Mulia Jakarta Timur - Isna Amalia; Windy Gustia Wardani (Yayasan Literasi Sains Indonesia, 2024)
The purpose of this study was to determine the effect of Physical Work Environment and Organizational Culture on Employee Job Satisfaction at PT Aneka Tambang Tbk UBPP Logam Mulia East Jakarta. This research uses quantitative methods. The sampling technique used is the Slovin technique with a sample size of 150 respondents. The tests carried out include validity test, reliability test, classical assumption test, linear regression test, correlation coefficient test, determination coefficient test, and hypothesis testing (t test and f test). The results of this study simultaneously have a significant effect on employee job satisfaction with regression Y = 5.346 + 0.171 X1 + 0.668 X2 + e, the correlation coefficient value of 0.837 means that simultaneously has a very strong level of relationship where the value is in the interval 0.800 - 1.000. While the coefficient of determination (Adjusted R Square) is 0.697 (69.7%). Based on this value, it shows that the percentage between the physical work environment variables (X1), and organizational culture (X2) affects employee job satisfaction (Y) by 69.7% while the rest (100% - 69.7%) = 30.3% is influenced by other variables that are not included. For hypothesis testing, the Fcount value of 172.250 is greater than the Ftable of 3.06, and the significant value is smaller than 0.05 (0.000 <0.05). Thus, the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This shows that there is a simultaneous significant influence between the variables of Physical Work Environment (X1) and Organizational Culture (X2) on Employee Job Satisfaction (Y) at PT Aneka Tambang Tbk UBPP Logam Mulia East Jakarta.